GENETIC DIFFERENTIATION AMONG POPULATIONS OF COTTUS SPINULOSUSKESSLER, 1872 (TELEOSTEI: COTTIDAE) (Scientific journal of the Fergana State University, 2023)
Three species of the genus Cottus (Cottus jaxartensis, Cottus nudus and Cottus spinulosus) have been recorded in the water bodies of Central Asia. Only one of these species - Cottus spinulosus - is found in the Fergana Valley. Three populations of this species were recorded in the Karadarya, Margilonsoy and Sokh rivers. When these populations were analyzed based on the mitochondrial COI barcode gene, it was revealed that they are located in separate clades in the phylogenetic family tree. Genetic distance between populations (K2P) was in the range of 0.62-0.93%.